Randomised controlled trial of the sliding hip screw versus X-Bolt Dynamic Hip Plating System for the fixation of trochanteric fractures of the hip in adults: a protocol study for WHiTE 4 (WHiTE4). Issue 1 (26th January 2018) - Griffin, Xavier L; Achten, Juul; Sones, William; Cook, Jonathan; Costa, Matthew L
Abstract : Introduction: Sliding hip screw fixation is well established in the treatment of trochanteric fractures of the hip. The X-Bolt Dynamic Hip Plating System builds on the successful design features of the sliding hip screw but differs in the nature of the fixation in the femoral head. A randomised pilot study suggested that the X-bolt Dynamic Hip Plating System might provide similar health-related quality of life while reducing the risk of revision surgery when compared with the sliding hip screw. This is the protocol for a multicentre randomised trial of sliding hip screw versus X-Bolt Dynamic Hip Plating System for patients 60 years and over treated for a trochanteric fracture of the hip. Methods and analysis: Multicentre, multisurgeon, parallel, two-arm, randomised controlled trial. Patients aged 60 years and older with a trochanteric hip fracture are potentially eligible. Participants will be randomly allocated on a 1:1 basis to either sliding hip screw or X-Bolt Dynamic Hip Plating System. Otherwise, all care will be in accordance with National Institute for Health and Care Excellence guidance. A minimum of 1128 patients will be recruited to obtain 90% power to detect a 0.075-point difference in EuroQol-5D health-related quality of life at 4 months postrandomisation. Secondary outcomes include mortality, residential status, revision surgery and radiographic measures. The treatment effect will be estimated using a two-sided t-test adjusted for age, gender and cognitive impairment based on an intention-to-treat analysis. Ethics and dissemination: National Research Ethics Committee approved this study on 5 February 2016 (16/WM/0001). The study is sponsored by the University of Oxford and funded through an investigator initiated grant by X-Bolt Orthopaedics. A manuscript for a high-impact peer-reviewed journal will be prepared, and the results will be disseminated to patients through local mechanisms at participating centres. Trial registration number: ISRCTN92825709 .